Synthesis, characterization and antibacterial activities of new substituted (1,3)oxazepine 1,5- diones - Omar J. Mahdi Al-Asafi; Mohammed G. Mukhlif (Genius Journals, 2022)
Novel Imine were prepared via the reaction of (p-chloro and p-methyl)aniline with (pnitro and p-methoxy) benzaldehyde and later engaged in a condensation reaction with 2- O-Acetylmalic anhydride in a dioxane as a solvent. The resulting products were found to be 1,3-oxazepine-1,5-diones and their derivatives. FT-IR , 1HNMR and C.H.N. spectra were used to confirm the structures of products. The antibacterial properties of these compounds were also examined
Keywords: Seven-Member; Antibacterial Activities; Oxazepine; Imine